2015
DOI: 10.3746/pnf.2015.20.4.238
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of L-Ornithine on the Phosphorylation of mTORC1 Downstream Targets in Rat Liver

Abstract: A non-protein amino acid, L-ornithine (Orn), has been shown to stimulate the urea cycle and tissue protein synthesis in the liver. The purpose of the current study was to assess whether Orn affects the mammalian target of rapamycin (mTOR) complex 1 (mTORC1) pathway, which is involved in protein synthesis. Primary cultured cells isolated from Wistar rat liver were incubated in an amino acid-free medium, followed by addition of Orn for 3 h. The cell lysate was subjected to immunoblotting to evaluate the phosphor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…mTORC1 is the primary representative of a signal-mediating molecule related to nutrient-sensing. Leucine, arginine, and methionine (or S-adenosylmethionine) have been demonstrated to stimulate (Wolfson et al, 2015;Chantranupong et al, 2016;Gu et al, 2017), and another report has shown that ornithine also activates mTORC1 (Kokubo et al, 2015). Thus, we initially suspected that mTORC1 is also involved in the amino-acid-dependent regulation of G6Pase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mTORC1 is the primary representative of a signal-mediating molecule related to nutrient-sensing. Leucine, arginine, and methionine (or S-adenosylmethionine) have been demonstrated to stimulate (Wolfson et al, 2015;Chantranupong et al, 2016;Gu et al, 2017), and another report has shown that ornithine also activates mTORC1 (Kokubo et al, 2015). Thus, we initially suspected that mTORC1 is also involved in the amino-acid-dependent regulation of G6Pase.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to leucine, ornithine also activates mTORC1 (Kokubo et al, 2015). We, therefore, treated cells with torin 1 again and evaluated the involvement of mTORC1 in the ornithine-mediated G6Pase transcription regulation.…”
Section: Ll Open Access Isciencementioning
confidence: 99%